Fostering independent learners: Kurikulum Merdeka, Merdeka Belajar, the student-centred learning approach and pedagogical reform - Kurniawan, I Gede Wahyu Antara (Journal of Language, Literature, Social and Cultural Studies, 2023)
This research uses document review and literature review methods. The document review was carried out by analyzing official documents related to the Independent Curriculum, such as Minister of Education, Culture, Research and Technology Regulation Number 34 of 2022 concerning National Standards for Junior High School Education and Regulation of the Minister of Education, Culture, Research and Technology Number 35 of 2022 concerning National High School Education Standards. The literature review was carried out by analyzing previous research writings about the Independent Curriculum, student-centred learning, and independent learning. The results of the analysis show that the Independent Curriculum and independent learning are closely related. The Independent Curriculum is an effort to realize independent learning. This can be seen from several main characteristics of the Independent Curriculum, such as: (a Focus on essential material that can be studied in depth. (b) Providing freedom to teachers and schools in developing curriculum and learning. (c) Accommodating students' needs and interests. Centred learning on students is one of the strategies that can be used to implement the Merdeka Curriculum. Student-centred learning emphasizes the active role of students in the learning process. Students are not only objects of learning, but also learning subjects who have an important role in determining the direction of learning. Implementation of the Merdeka Curriculum and independent learning requires a change in the learning paradigm. Teachers must shift from their role as transmitters of information to facilitators of learning. Teachers must be able to create a learning environment that supports students to learn actively and independently.